Strategi Pemasaran Radio Solopos 103 FM dalam Meningkatkan Jumlah Pengiklan - Hilmi, Naufal; Harnita, Pratiwi Cristin; Abraham, Rendy Hermanto (Jurnal Ilmiah Wahana Pendidikan, 2025)
This research aims to find out how the marketing strategy of Radio Solopos 103 FM in increasing the number of advertisers. The approach used is qualitative with data collection techniques from interviews, observation, and documentation. The research informants are marketing staff from Radio Solopos 103 FM. Findings from the results of data collection will be further analyzed to gain an in-depth understanding of the marketing strategies carried out by Radio Solopos in increasing advertisers. The results obtained from this research are expected to be able to add and enrich the knowledge of readers, especially in the field of Communication Science and can be a reference for learning in the field of Communication Science in mass media marketing communication strategies. This research is also expected to be an evaluation, input, thought, and consideration for Radio Solopos 103 FM in implementing marketing strategies to increase the number of advertisers. In this research, the promotion mix is a unique blend of public relations, sales promotion, personal selling, and advertising that a business uses to achieve its advertising and marketing objectives. The promotion mix is used as a reference for Radio Solopos 103 FM's marketing strategy activities in increasing the number of advertisers.